Laser microprobe mass analysis (LAMMA) of pyridine adsorbed on some clay minerals from Turkey - Waele, J. K.; Adams, F. C.; AKYÜZ, ZEKİ TANIL; AKYÜZ, SEVİM (Kluwer Academic Publishers, 1985)
Using laser microproble mass analysis (LAMMA), it is possible to characterize the inorganic composition of clays and to study adsorption phenomena. Natural sepiolite, (Na-sepiolite), montmorillonite and saponite samples from Anatolia (Turkey) have been investigated. All the clays gave different fingerprint mass spectra which allowed a quick estimation of the relative amounts of exchangeable cations as well as the trace contaminants and the homogeneity of their distribution. The adsorption behaviour of these clays for pyridine was also studied and it appeared that pyridine molecules penetrated the inner layers, as well as being adsorbed on the external surface.
Keywords: adsorption; laser microprobe mass analysis (LAMMA); clay